Quality control and interest of the determination of anti-CCP antibodies and rheumatoid factor in the diagnosis of rheumatoid arthritis........ - AMOUSSOU, NATHALIE GISELE; GOUNONGBE, MARCELLE COLETTE MARIE; DOUGNON, T. VICTORIEN; ZOMALHETO, COSSI ZAVIER; LOKO, CHRISTIAN FRÉDÉRIC SIMPLICE; BIGOT, KOFFI ANDRÉ (My University, 2016)
The rheumatoid arthristis (RA) is an auto-immune rhematic and chronic inflammatory disease characterized by joints domage.
Keywords: anti-CCP rheumatoid factor; rheumatoid arthristis; biological diagnosis